“A PROSPECTIVE STUDY TO EVALUATE THE ROLE OF STEREOTACTIC BIOPSY IN THE DIAGNOSIS OF BRAIN LESIONS” - Dr Amol Aaglave; Dr Anand Sharma; Dr Deepak Jaiswal; Dr Avinash Sharma; Dr Vinaya Chaudhary; Dr Avdhesh Shukla (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Background: Brain lesions, including neoplastic, inflammatory, infectious, and vascular pathologies, pose significant diagnostic challenges. Stereotactic biopsy has emerged as a valuable technique for diagnosing intracranial lesions that are inaccessible to conventional surgical approaches. Despite advances in imaging, histopathological confirmation remains crucial for determining appropriate management strategies. This study aims to evaluate the effectiveness, safety, and diagnostic yield of stereotactic brain biopsy in patients with suspected brain lesions.Methods: A prospective observational study was conducted at the Department of Neurosurgery, J.A. Group of Hospitals and G.R. Medical College, Gwalior, India, between January 2023 and June 2025. Thirty patients with suspected brain lesions, identified through CT or MRI, underwent stereotactic biopsy. Preoperative neuroimaging was used to localize the lesions, and histopathological analysis was performed on biopsy samples. The diagnostic accuracy, post-operative complications, and impact on patient management were evaluated.Results: Among the 30 patients, the most common histopathological diagnoses were tuberculoma (31%), astrocytoma (13.8%), and metastasis (13.8%). The overall diagnostic accuracy of stereotactic biopsy was 93.3%, with two non-diagnostic results. Post-operative complications were minimal, including new or worsened neurological deficits (13.3%), infections (6.7%), and seizures (10%). Notably, 60% of patients experienced improved functional status following the procedure.Conclusion: Stereotactic biopsy is a safe, effective, and highly accurate diagnostic tool for brain lesions, especially in cases involving deep-seated, multifocal, or inaccessible lesions. The procedure is associated with a low risk of significant complications, and its high diagnostic yield significantly impacts patient management and treatment decisions.